Impact of Conservation Agriculture on Wheat Growth, Productivity and Nutrient Uptake in Maize–Wheat–Mungbean System - Ghosh, Sonaka; Das, T. K.; Shivay, Y. S.; Bhatia, Arti; Sudhishri, Susama; Yeasin, Md (International Journal of Bio-resource and Stress Management, 2022)
Conservation agriculture (CA) involving minimum mechanical soil disturbance, permanent soil cover with crop residue mulch and diversified crop rotation, plays a crucial role in sustainable crop production. A field experiment was conducted at ICAR-Indian Agricultural Research Institute, New Delhi during rabi seasons (November–April) of 2018–19 and 2019–20 in wheat involving maize-wheat-mungbean system to assess the effects of CA on crop productivity, nutrient uptake and profitability. Results showed that CA-based practices with residue retention resulted in higher yield as well as economic benefits when compared to conventional tillage (CT). Wheat yield parameters in CA were greater than in CT. The CA-based practices improved wheat grain and straw yield to the tune of 7.2–27.1% and 5.7–20.6%, respectively compared to CT practice. The CA-based practices with residue retention with 100% N registered 9.7% higher cost of cultivation, but resulted in 24.3–35.1% higher net returns than CT. Among CA-based practices, the plots under permanent broad bed with residue with 100% N (PBB+R+100N) resulted in ~27% higher wheat grain yield compared to CT. The PBB+R+100N plots also had considerably greater nutrient uptake and net returns than CT plots. The CA practice involving PBB+R+100N was found to be more productive, remunerative and could potentially boost up the wheat productivity and profitability under maize-wheat-mungbean system in north-western Indo-Gangetic Plains of India.